Round table on J.-L. Nancyʼs book «Being singular plural» - Malyshkin, Evgenii V.; Pogrebniak, Aleksandr A.; Gafarova, Julia J. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
In June 2019, in the city of Polack (Belarus), as part of the bilateral Belarus – Russian research project «Distribution of knowledge in a network society: the interaction of archaic and modern forms», a round table was held. It was devoted to the text of the famous French philosopher J.-L. Nancy «Being singular plural» (Être singulier pluriel, 1996). The key concept of the project which is distributed knowledge, is well defined with what J.-L. Nancy calls cum-. Explaining the consistency of the J.-L. Nancy’s text with the chosen research perspective, the round table participants expand the context of the use of concepts such as contingency, distribution, Mitsein, trying to comply with the claim of J.-L. Nancy’s book wich is (re)writing first philosophy.